FAMILY ENVIRONMENT IN CHILDREN'S UPbringing AND ITS INFLUENCE ON SOCIAL CONSCIOUSNESS. (Universal International Scientific Journal, 2026)
This article highlights the role of parents in raising children in the formation of a mature personality, relying on artistic, spiritual and religious literature. In addition, the impact of gender stereotypes on the minds of children, their social perception and value system is analyzed from a scientific and psychological perspective, justifying the need to raise a child as a spiritually mature and mature person through the family environment, national heritage, as well as literary sources.
Keywords: child rearing; family environment and psychology; social consciousness